A novel indication for a method in the treatment of lumbar tuberculosis through minimally invasive extreme lateral interbody fusion (XLIF) in combination with percutaneous pedicle screws fixation in an elderly patient: A case report. Issue 48 (November 2016) - Wang, Qiyou; Xu, Yichun; Chen, Ruiqiang; Dong, Jianwen; Liu, Bin; Rong, Limin
Abstract: Rationale: To describe a novel indication for a method through minimally invasive extreme lateral interbody fusion (XLIF) in combination with percutaneous pedicle screwsfixation in the treatment of lumbar tuberculosis (TB) in an elderly patient, and its clinical efficacy and feasibility. Lumbar TB is a destructive form of TB. Antituberculous treatment should be started as early as possible. In some circumstances, however, surgical debridement with or without stabilization of the spine appears to be beneficial and may be recommended. Surgeries through the approach of anterior or posterior are still challenging and often involve some complications. Patient concerns: The case is a 68-year-old female who was misdiagnosed as simple vertebral compression fracture and underwent L1 and L2 percutaneous vertebroplasty in another hospital 7 years ago. He complained of lumbosacral pain for 1 month this time. Magnetic resonance imaging (MRI) and computed tomography (CT) showed intervertebral space in L1/2 was seriously damaged like TB. Diagnoses: Lumbar tuberculosis Interventions: Antitubercular drugs, mini-invasive debridement with XLIF in combination with percutaneous pedicle screwsfixation was performed. This patient was followed up for 12 months. Outcomes: No obvious complication occurred during the operation and the wound healed well. Oswestry Disability Index (ODI: 56 vs 22) and visual analog scale (VAS: 4 vs 0) score significantly decreased atfinal follow-up of 12 months. Obvious recovery of kyphosis angle was found postoperatively (post: 14.8° vs pre: 33.5°). No recurrent infection occurred at the last follow-up. Lessons: Mini-invasive surgery by debridement through XLIF and percutaneous pedicle screwsfixation may be an effective and innovative treatment method for lumbar TB in the elderly.